Pengembangan Sistem Informasi Akuntansi Berbasis Web pada Sekolah Menengah Pertama Menggunakan Metode ERP - Larita Ayu Wahyuni S; Mustaqiem Mustaqiem (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2022)
The payment of Education Development Donations (SPP) system at Sampit 9 Public Middle School is still done manually, both in transactions and in the data recapitulation process, causing the process of recording payments and recapitulating payments to be slow and potentially causing errors in data collection. Presentation of information and management reporting is also slow. This study proposes an application model that supports the concept of a database system so that the processing of SPP payments and management of financial reports runs automatically and quickly. The Web-based system was developed using the Waterfall development method, and was built using the PHP programming language and MySQL database. System functions in the form of student data collection, tuition payments, General Journals, Accounting Journals, Profit and Loss Reports, Trial Balance, and Tuition Payment Reports are confirmed through the Blackbox testing technique. The functional test results show that these functions are running validly. The developed computerized system can also help admin performance to be more accurate and efficient in managing SPP payment data with financial reports based on an accounting system.Keywords: application software; database system; Waterfall, Blackbox Testing AbstrakSistem pembayaran Sumbangan Pembinaan Pendidikan (SPP) di SMP Negeri 9 Sampit masih dilakukan secara manual, baik dalam transaksi maupun dalam proses rekapitulasi data, menyebabkan proses pencatatan pembayaran serta rekapitulasi pembayaran menjadi lambat dan berpotensi menimbulkan kekeliruan dalam pendataan. Penyajian informasi dan pelaporan manajemen juga menjadi lambat. Penelitian ini mengusulkan model aplikasi yang mendukung konsep sistem basis data agar pengolahan pembayaran SPP dan pengelolaan laporan kuangan berjalan otomatis dan cepat. Sistem berbasis Web dikembangkan menggunakan metode pengembangan Waterfall, dan dibangun menggunakan bahasa pemrograman PHP dan database MySQL. Fungsi-fungsi sistem berupa pendataan siswa, pembayaran SPP, Jurnal Umum, Jurnal Akuntansi, Laporan Laba Rugi, Neraca Saldo, serta Laporan Pembayaran SPP dikonfirmasi melalui teknik pengujian Blackbox.  Hasil uji fungsional menunjukkan fungsi-fungsi tersebut telah berjalan secara valid. Sistem terkomputerisasi yang dikembangkan juga dapat membantu kinerja admin agar lebih akurat dan efisien dalam pengelolaan data pembayaran SPP dengan laporan kuangan berdasarkan sistem akuntansi.